Konkordiebog og Kirkeordinans - Dreyer, Rasmus H.C. (Dansk Teologisk Tidsskrift, 2023)
The Book of Concord (1580) is the normative collection of confessions in the worldwide Lutheran Church. The present Danish Lutheran Church is an exception due to Danish King Frederik II’s rejection of the Book of Concord in 1580. This article reviews the historical background for the Book of Concord and especially the history and theology of the Formula Concord. It pays special attention to the use of Luther and Confessio Augustana (Invariata) as theological authorities in Formula Concord. In Denmark, Philippist theology was the predominant way of thinking theology in the late 16th century, yet it is not barely the contrast to a presumed Gnesiolutheran biased Formula Concord, which can explain the Danish rejection of Book of Concord and Formula Concord. Denmark already had a collection of confessions, a corpora doctrinae, the article argues, in form of its Church Ordinance (1537/39) (co-authored by Wittenberg-theologian Bugenhagen) and i.a. the Niels Hemmingsen authored legislative documents, De Tabella de Coena Domini (1557) and the Foreigner’s Articles (1569). Furthermore, Danish foreign policy was to a greater extent than the other Lutheran countries bound by an expectation of Catholic reaction and for that reason the need for a pan-Protestant alliance. In this way, the Danish process of fixing a Lutheran confession resulted in a more pragmatic way of being a confessional Lutheran church and state.